The postwar rapprochement of Malaya and Japan, 1945-61 the roles of Britain and Japan in South-East Asia - Tomaru, Junko (St. Antony's series, 2000)
Why was the postwar Malayo-Japanese rapprochement relatively quick, despite the bitter memories of Japan's wartime occupation and Britain's determination to maintain imperial control of its South-East Asian stronghold? Junko Tomaru sheds new light on the tripartite economic and political relations of Malaya, Japan, and Britain as the suzerain of Malaya in the immediate postwar period. The development of postwar Malayo-Japanese relations from the resumption of unofficial economic relations to the establishment of formal diplomatic rapprochement soon after the decolonization of Malaya is closely analysed. The author thus emphasizes the importance of the British role in facilitating the rapprochement and the enthusiasm of Malayan and Japanese leaders in promoting cordial relations. This presents a significant revision of the predominant approach concentrating on the role of the US in facilitating the Japanese return to South-East Asia. The continuity in prewar and postwar Japanese involvement in Malaya and the psychological dimension of the tripartite postwar relations are also revealed.